From the editors - Esterhuyse, Abel; Liebenberg, Ian (Scientia Militaria - South African Journal of Military Studies, 2012)
Numerous challenges confront armed forces at present, and in a complex world, they need to understand the nature of these challenges. The challenges are in many cases related either to threats emanating from the foreign policy environment or to vulnerabilities from the domestic political environment. The understanding of the nature of these threats is a key factor in helping armed forces to organise, equip and train themselves in order to deal with these issues. Most of the debates about armed force and the use thereof, thus, focus on understanding what ought to be done and how it should be done. Linking these two questions to the availability of resources and the defence budget in particular, is the concentrated essence of military science and strategy. The articles in this edition of Scientia Militaria – South African Journal of Military Studies reflect the need for armed forces to understand what ought to be done and how it should be done. In addition, it touches on the effect of these two factors on the institutional nature of armed forces.